Comparison the Strength of Midship Structures With Margin Plate and Without Margin Plate - Andi Ardianti; Rosmani Munandar; Haryono Haryono; Ganding Sitepu; Hamzah Hamzah (EPI International Journal of Engineering, 2021)
Margin plate is a part of bottom construction that joint the floor and frame construction of the ship, so the inner bottom plate will be installed cut off on the margin plate. Lately the bottom construction of the ship tends not to use the margin plate. The ship is currently built with an inner bottom plate continuously from the left side to the right side of the ship.This study aims to determine the transversal and longitudinal strength ratio of ships with and without margin plate. The analysis was carried out by using Finite Element Method so-called ANSYSTM. The result shows if the loadvariatied 0.2 x maximum load on the calculation of the transverse strength of the ship, the stress value on the ship model with a margin plate was 9.6242 (N/mm2) and on the ship model without margin plate was 8.4739 (N/mm2) under conditions 100%. The results of the comparison due to bottom load averaged 15.82%. The difference in stress due to the effect of deck loads was an average of 13.49% while the effect of side loads was on average 8.74%. The longitudinal strength of the ship was also a varied of every increase of 0.2 x maximum moment with a review point of meeting between bottom plate and bilga plate for the ship model without margin plates using the Multi Point Constraint (MPC) method looking for results in sagging conditions of 12,443 (N / mm2) and the hogging condition was -11.045 (N / mm2) at 100% x maximum moment load conditions. So that the ship model with a margin plate sagging condition was 23,189 (N / mm2) and hagging condition was -20,585 (N / mm2). The results showed the stress that occurred in the ship model without using margin plate was better to withstand the transverse and longitudinal strength of the ship compared to the ship model with the margin plate.